Polyamine and Isoamylamine Levels in Peripheral Blood Cells and Plasma as Biomarkers of Structural and Functional Alterations in Acute Myocardial Infarction and Chronic Heart Failure Patients - José Manuel Rubín; Lorena Suárez; Begoña Cantabrana; Eva Barreiro-Alonso; Ignacio Rodríguez-Uña; Manuel Sánchez (Applied Sciences)
Polyamines are essential biological compounds that play crucial roles in various physiological processes, including cardiovascular function. This study explored polyamine levels in peripheral blood cells and plasma from patients with acute myocardial infarction (AMI) and chronic heart failure (CHF), aiming to assess their value as biomarkers for cardiac diseases. A total of 129 individuals participated, comprising healthy controls and patients diagnosed with AMI or CHF. Polyamine concentrations were measured and analysed alongside standard clinical and biochemical markers of cardiac diseases. The results showed distinct patterns of polyamine alteration in AMI patients; putrescine levels were reduced in mononuclear cells, while isoamylamine levels were elevated in erythrocytes and plasma. In contrast, CHF patients had consistently low levels of all measured polyamines in erythrocytes and plasma, accompanied by high isoamylamine levels. Statistical analyses revealed significant correlations between polyamine levels and clinical indicators such as left ventricular ejection fraction, diastolic blood pressure, and troponin. Discriminant function analysis effectively distinguished between the control, AMI, and CHF groups based on their polyamine profiles. These findings suggest that an altered polyamine metabolism is associated with cardiovascular disease and support the potential of blood polyamine profiling as a non-invasive diagnostic and monitoring tool. Further research is warranted.